A study on structural design and analysis of small wind turbine blade with natural fibre(flax) composite. (3rd March 2016) - Park, Hyunbum
Abstract : In recent years, there has been a growing interest in the use of naturally sourced fibres for use in composites design and manufacture. In this work, a structural design on 1-kW-class horizontal axis wind turbine blade using natural flax fibre composite is performed. The structural design results of flax/epoxy composite blade are compared with the design results of glass/epoxy composite blade. In order to evaluate the structural design of the composite blade, the structural analysis was performed by the finite element method. Through the structural analyses, it is confirmed that the designed blade using natural composite is acceptable for structural safety, blade tip deflection, structural stability, resonance possibility and weight.